The practical interpretation of the categorical imperative: a defense - Dimitriu, Cristian (2013)
The article compares two different interpretations of Kant's categorical imperative −the practical and the logical one− and defends the practical one, arguing that it is superior because it rejects cases of free riding without necessarily rejecting cases of coordination or timing. The logical interpretation, on the other hand, leads to the undesirable outcome that it does not reject immoral cases of free riding, and to the desired outcome that it does not reject maxims of coordination/timing. Given that neither of them rejects maxims of coordination/timing (they are similar in that sense) and only the practical interpretation rejects free riding, the logical interpretation should be rejected.